Low-temperature electrical discharge through solid xenon - Gordon, E.B.; Matyushenko, V.I.; Sizov, V.D.; Smirnov, B.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The uniform self-sustained electrical discharge through solid xenon has been realized and studied. The multiplication of electrons proceeds in the noble gas above the xenon crystal interface whereas a positive feedback is realized at the account of multiple exciton formation by excess electrons drifted through the crystal: molecular excitons emit VUV photons which knocked out secondary electrons from photosensitive cathode. The discharge was stimulated by short electrical spark along the sample axes. The discharge electrical properties as well as the spectra of solid xenon electroluminescence in UV and visible have been studied. Electric discharge in solid xenon was proved to be an effective source of UV radiation and a convenient tool to study the processes involving excitons and electrons in solid xenon at high pressures.